2014
DOI: 10.7554/elife.03939
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic competition during the transcription cycle results in stochastic RNA processing

Abstract: Synthesis of mRNA in eukaryotes involves the coordinated action of many enzymatic processes, including initiation, elongation, splicing, and cleavage. Kinetic competition between these processes has been proposed to determine RNA fate, yet such coupling has never been observed in vivo on single transcripts. In this study, we use dual-color single-molecule RNA imaging in living human cells to construct a complete kinetic profile of transcription and splicing of the β-globin gene. We find that kinetic competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
252
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(263 citation statements)
references
References 63 publications
11
252
0
Order By: Relevance
“…The previously described construct HIV-2-noGag-BglSL (21) is referred to as 2-noGag-BSL for clarity in the present report; this HIV-2-based construct contains two stop-codon mutations in the gag gene-one at codon 17 of Gag in MA and one at codon 171 of CA-to abolish Gag expression (21). Construct globin-MSL was modified from r-Cfp-betaglobin (27), which encodes a β-globin gene under the control of the tet promoter. The β-globin gene includes introns, and a CeFP gene was fused to the end of exon 3; additionally, intron 2 and 3′ UTR contain stem-loop sequences recognized by bacteriophage PP7 and MS2 coat proteins, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The previously described construct HIV-2-noGag-BglSL (21) is referred to as 2-noGag-BSL for clarity in the present report; this HIV-2-based construct contains two stop-codon mutations in the gag gene-one at codon 17 of Gag in MA and one at codon 171 of CA-to abolish Gag expression (21). Construct globin-MSL was modified from r-Cfp-betaglobin (27), which encodes a β-globin gene under the control of the tet promoter. The β-globin gene includes introns, and a CeFP gene was fused to the end of exon 3; additionally, intron 2 and 3′ UTR contain stem-loop sequences recognized by bacteriophage PP7 and MS2 coat proteins, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Work from the Shav-Tal laboratory (Brody et al 2011) measured the accumulation of snRNPs during splicing and demonstrated that the elongation machinery does not "wait" for each splicing event to go to completion but rather moves ahead so that more introns accumulate. Likewise, adding more introns did not measurably change the rate of transcript synthesis, indicating that elongation proceeds independently of splicing (Brody et al 2011).Further evidence of the relationship between elongation and splicing rates was obtained by Coulon et al (2014). Using dual labeling of intronic and exonic RNA, one is able to separate the kinetics of elongation, splicing, and cleavage.…”
mentioning
confidence: 75%
“…Further evidence of the relationship between elongation and splicing rates was obtained by Coulon et al (2014). Using dual labeling of intronic and exonic RNA, one is able to separate the kinetics of elongation, splicing, and cleavage.…”
mentioning
confidence: 86%
“…Notably, this allows the simultaneous following of different RNA species in vivo, or it can be used to analyze the kinetics and precise control of mRNA splicing and translation (Martin et al, 2013;Coulon et al, 2014;Halstead et al, 2015).…”
Section: Fluorophore-binding Rna Motifsmentioning
confidence: 99%